Consumer Trust and Brand Authenticity in Transnational Tourism Marketing: Effects on Participation Rates in Small Sports Events and Overall Destination Appeal - Shuangpeng Lu; Johan Afendi Bin Ibrahim; Lina Munirah Binti Kamarudin, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This research investigates the interplay between consumer trust, brand authenticity, brand loyalty, and personal involvement in influencing participation rates in small sports events within transnational tourism marketing. By examining how these factors collectively shape tourist decision-making and destination attractiveness in sports tourism, the study provides new insights into consumer behaviour. A quantitative approach was utilized, with a structured questionnaire distributed to 800 participants, yielding 470 valid responses analysed using SPSS. Regression and mediation analyses were conducted to explore the direct and mediated effects of consumer perceptions on participation rates, while also considering the moderating role of personal involvement. The findings reveal significant positive relationships between consumer trust, brand authenticity, brand loyalty, and participation rates in small sports events, with brand loyalty mediating the effects of consumer trust and brand authenticity on participation. Furthermore, personal involvement was found to moderate these relationships, enhancing the impact of consumer perceptions on tourist behaviour. This study contributes to theoretical advancements by integrating multiple dimensions of consumer behaviour and destination marketing in the context of small sports events. It underscores the importance of authenticity and trust in shaping tourist preferences and behaviours while offering practical guidance for destination marketers on increasing tourism participation and destination appeal through strategic consumer engagement. The findings advocate for the inclusion of small sports events in transnational tourism marketing strategies to promote sustainable tourism development and foster community engagement through sports tourism initiatives.